Soil cultivation methods rather than catch crop species enhance bacterial diversity in soil over a three-year experiment - Řezáčová, Veronika; Šimon, Tomáš; Némethová, Ema; Saska, Pavel; Mayerová, Markéta (Scientific reports, 2025)
Growing catch crops can improve soil health by enhancing microbial diversity, but their impact may be constrained by how they are managed. This study examined the effects of different catch crop species and soil cultivation methods on bacterial and fungal diversity, and total soil microbial biomass. A 3-year field experiment on Luvi-haplic Chernozem included two catch crop species and five mixtures (further catch crop species) and three cultivation methods (ploughing, reduced tillage and no tillage), resulting in 21 treatments (7 catch crop species x 3 soil cultivations). Soil samples (0–15 cm depth) were collected annually in autumn and spring since 2021 to 2024. Microbial biomass was assessed using the chloroform fumigation extraction method, while fungal and bacterial diversity was analysed by amplifying and sequencing the ITS2 region of rDNA and the V4 region of the 16 S rRNA gene for fungi and bacteria, respectively, via Illumina paired-end amplicon sequencing. Soil cultivation methods affected bacterial diversity, with reduced tillage showing higher diversity and evenness than ploughing, though neither differed from no-till. However, no effect was observed on fungal diversity, including AM fungi, or microbial biomass. Catch crop species did not significantly impact microbial diversity or biomass. Neither cultivation method nor catch crop species influenced the ratios of functional trophic groups, such as pathogens, saprotrophs or symbionts. This study underscores the critical role of soil management practices—especially reduced tillage—in promoting soil health, primarily through the enhancement of bacterial diversity.